The Effect of Liquid Organic Fertilizer Concentration of Gamal Leaves on The Growth and Production of Sawi (Brasicca Juncea L.) - Anti, Wa Ode; Rahim, Abdul; Hidayat, La Ode; Ramisa, Starni; Sifa, Muhammad (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2023)
This research aims to study the effect of gamal leaf POC concentration on the growth and production of mustard greens. In addition, to study the POC concentration of gamal leaves which has the best influence on the best growth and production of mustard greens. This research was carried out in Lasalepa Village, Lasalepa District, Muna Regency, Southeast Sulawesi Province. This research was carried out for three months, from June to September 2022. The materials used in this research were mustard seeds, chicken manure, gamal leaves, EM4, brown sugar, pure water and pesticides. The tools used consisted of machetes, hoes, scales, meters, gembors, sprayers, buckets, digital thermometers, raffiah ropes, cameras and writing instruments. This research was structured based on a Randomized Block Design (RAK) which consisted of five treatment levels, namely: without POC of gamal leaves, G1 = 50 ml POC of gamal leaves/liter of water, G2 = 100 ml of POC of gamal leaves/liter of water, G3 = 150 ml POC gamal leaves/liter of water, and, and G4 = 200 ml POC of gamal leaves/liter of water. The parameters observed in this study consisted of plant height (cm), number of leaves (strands), and plant fresh weight (g). The thesis shows that POC of gamal leaves with different concentrations has an effect on plant height, number of leaves and fresh weight per plant. Gamal leaf POC with a concentration of 200 ml/l water provided the best growth and production of mustard greens with a production of 217.39 g/plant or 36.23 t/ha.